Methods for constructing system-wide parameters and keys for NTRU PRIME UKRAINE 5 – 7 stabvility levels. Product form - Gorbenko, I.D.; Kachko, O.G.; Gorbenko, Yu. I.; Stelnik, I.V.; Kandy, S.O.; Yesina, M.V. (Radiotekhnika, 2018)
The research was carried out and the development of an effective practical algorithm for the construction of system-wide parameters and keys of cryptographic transformations such as asymmetric ciphers for a special form of setting the Product Form polynomial was performed. The experimental confirmation of the built-in system-wide parameters for 5 – 7 stability levels NTRU PRIME UKRAINE, taking into account a combined attack. is given.